Biokonsentrasi dan Bioakumulasi Mercury (Hg) Pada Lamun Enhalus Acoroides Di Teluk Kayeli Kabupaten Buru Provinsi Maluku - R. Fakaubun, Fahrul; Male, Yusthinus T; Selanno, Debby A. J. (Indonesian Journal of Chemical Research, 2020)
Gold reserves on Gunung Botak (Bald Mountain), Buru Island, were discovered in 2011. Since then, thousands of illegal miners have used amalgamation methods to extract gold in the areas of Gunung Botak and Gogrea, Buru Island. The resulting waste is disposed of into the environment directly without any treatment process so it is very dangerous for humans and the environment. This research was conducted to determine the ability of the Enhalus acoroides type of seagrass to accumulate heavy metal mercury (Hg) in the aquatic environment. This research shows that the heavy metal mercury has been distributed in the water sediments along Kayeli Bay. Mercury bio-concentration (accumulation) Gunung Botak, Kayeli Bay, Mercury (Hg), bioconcenstration, Seagrass, Enhalus acoroides, Kayeli Baywas found in Enhalus acoroides seagrass, in leaves (0.0243-0.0373 mg/Kg), and in rhizomes (0.0453-0.0663 mg/Kg). This result shows that the Kayeli Bay ecosystem has been contaminated with mercury.